Changes in estimated glomerular filtration rate over time in South African HIV‐1‐infected patients receiving tenofovir: a retrospective cohort study. Issue 1 (10th April 2017) - De Waal, Reneé; Cohen, Karen; Fox, Matthew P; Stinson, Kathryn; Maartens, Gary; Boulle, Andrew; Igumbor, Ehimario U; Davies, Mary‐Ann
Abstract: Introduction : Tenofovir has been associated with decline in kidney function, but in patients with low baseline kidney function, improvements over time have been reported. Additionally, the magnitude and trajectory of estimated glomerular filtration rate (eGFR) changes may differ according to how eGFR is calculated. We described changes in eGFR over time, and the incidence of, and risk factors for, kidney toxicity, in a South African cohort. Methods : We included antiretroviral‐naïve patients ≥16 years old who started tenofovir‐containing antiretroviral therapy (ART) between 2002 and 2013. We calculated eGFR using the Modification of Diet in Renal Disease (MDRD), Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI), and Cockcroft‐Gault equations. We described changes in eGFR from ART initiation using linear mixed effects regression. We described the incidence of eGFR <30 mL/min on treatment, and identified associations with low eGFR using Cox regression. Results : We included 15156 patients with median age of 35.4 years (IQR 29.9–42.0), median CD4 cell count of 168 cells/µL (IQR 83–243), and median eGFR (MDRD) of 98.6 mL/min (IQR 84.4–115.6). Median duration of follow up on tenofovir was 12.9 months (IQR 5.1–23.3). Amongst those with a baseline and subsequent eGFR  available, mean eGFR change from baseline at 12 months was −4.4 mL/min (95% CI −4.9 to −4.0), −2.3 (−2.5 to −2.1), and 0.6 (0.04 to 1.2) in those with baseline eGFR ≥90 mL/min; and 11.9 mL/min (11.0 to 12.7), 14.6 (13.5 to 15.7), and 11.0 (10.3 to 11.7) in those with baseline eGFR <90 mL/min, according to the MDRD, CKD‐EPI (n = 11 112), and Cockcroft‐Gault (n = 9 283) equations, respectively. Overall, 292 (1.9%) patients developed eGFR <30 mL/min. Significant associations with low eGFR included older age, baseline eGFR <60 mL/min, CD4 count <200 cells/µL, body weight <60 kg, and concomitant protease inhibitor use. Conclusions : Patients on tenofovir with baseline eGFR ≥90 mL/min experienced small but significant declines in eGFR over time when eGFR was estimated using the MDRD or CKD‐EPI equations. However, eGFR increased in patients with eGFR <90 mL/min, regardless of which estimating equation was used. Decreases to below 30 mL/min were uncommon. In settings with limited access to laboratory testing, monitoring guidelines should consider focusing on higher risk patients.